2019
DOI: 10.1111/mmi.14321
|View full text |Cite
|
Sign up to set email alerts
|

DrRecQ regulates guanine quadruplex DNA structure dynamics and its impact on radioresistance in Deinococcus radiodurans

Abstract: Summary The GC‐rich genome of Deinococcus radiodurans contains a very high density of putative guanine quadruplex (G4) DNA motifs and its RecQ (drRecQ) was earlier characterized as a 3′→5′ dsDNA helicase. We saw that N‐Methyl mesoporphyrin IX (NMM), a G4 DNA binding drug affected normal growth as well as the gamma radiation resistance of the wild‐type bacterium. Interestingly, NMM treatment and recQ deletion showed additive effect on normal growth but there was no effect of NMM on gamma radiation resistance of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…The unwinding of double strand DNA substrates (with 5' overhang as well as 3' overhang) 448 by drDnaB (2µM) in the presence of different combinations of 1 mM ATP and 2 µM PprA 449 was monitored using fluorescent resonance energy transfer (FRET) approach using 96-well 450 plates as described in (Khairnar et al, 2019). In brief, the substrates used were FAM and 451 BHQ labelled complementary oligonucleotides (Table S1).…”
Section: Dna Helicase Activity Assay 447mentioning
confidence: 99%
See 1 more Smart Citation
“…The unwinding of double strand DNA substrates (with 5' overhang as well as 3' overhang) 448 by drDnaB (2µM) in the presence of different combinations of 1 mM ATP and 2 µM PprA 449 was monitored using fluorescent resonance energy transfer (FRET) approach using 96-well 450 plates as described in (Khairnar et al, 2019). In brief, the substrates used were FAM and 451 BHQ labelled complementary oligonucleotides (Table S1).…”
Section: Dna Helicase Activity Assay 447mentioning
confidence: 99%
“…The 459 fluorescence signals were monitored at an interval of 30 seconds using microplate reader 460 (Biotek Synergy H1). 461Similarly, gel-based DNA helicase activity assay of drDnaB was carried out as descried in 462(Khairnar et al, 2019). In brief, the 3′ overhang substrate was made by annealing the [ 32 PDas and Misra, 2012).…”
mentioning
confidence: 99%
“…RecQ belongs to a conserved family of helicases important for genome maintenance [ 30 ] (see above, WRM and BLM). The RecQ family of helicases can unwind G-quadruplex structures [ 31 , 32 ]. Nevertheless, while in vitro approaches have shown that bacterial RecQ can resolve G4s, it is unclear whether it plays a role in vivo [ 27 ].…”
Section: Introductionmentioning
confidence: 99%